O'Corry-Crowe et al 2016 - Biology Letters - microsat data - O'Corry-Crowe, Gregory; Mahoney, Andrew R.; Suydam, Robert; Quakenbush, Lori; Whiting, Alex; Lowry, Lloyd; Harwood, Lois (Dryad Digital Repository, 2016)
microsatellite data for beluga whales